2021
DOI: 10.3390/ijms222312824
|View full text |Cite
|
Sign up to set email alerts
|

The Flavonoid Biosynthesis Network in Plants

Abstract: Flavonoids are an important class of secondary metabolites widely found in plants, contributing to plant growth and development and having prominent applications in food and medicine. The biosynthesis of flavonoids has long been the focus of intense research in plant biology. Flavonoids are derived from the phenylpropanoid metabolic pathway, and have a basic structure that comprises a C15 benzene ring structure of C6-C3-C6. Over recent decades, a considerable number of studies have been directed at elucidating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
197
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 384 publications
(289 citation statements)
references
References 159 publications
(207 reference statements)
0
197
0
2
Order By: Relevance
“…The synthesis of quercetin is heavily linked to the general flavonoid biosynthetic pathway in plants. Therefore, it is dependent on the transcription regulation of all pathways leading up to anthocyanins, as they represent products that in their biosynthesis require the most steps of the flavonoid metabolism [ 42 ]. Transcription factors such as the basic helix–loop–helix (bHLH), R2R3-MYB, and the WD40 proteins lead to the activation, and differential temporal and spatial expression of the structural genes necessary in the biosynthesis [ 22 , 42 , 43 ].…”
Section: Quercetinmentioning
confidence: 99%
See 2 more Smart Citations
“…The synthesis of quercetin is heavily linked to the general flavonoid biosynthetic pathway in plants. Therefore, it is dependent on the transcription regulation of all pathways leading up to anthocyanins, as they represent products that in their biosynthesis require the most steps of the flavonoid metabolism [ 42 ]. Transcription factors such as the basic helix–loop–helix (bHLH), R2R3-MYB, and the WD40 proteins lead to the activation, and differential temporal and spatial expression of the structural genes necessary in the biosynthesis [ 22 , 42 , 43 ].…”
Section: Quercetinmentioning
confidence: 99%
“…Therefore, it is dependent on the transcription regulation of all pathways leading up to anthocyanins, as they represent products that in their biosynthesis require the most steps of the flavonoid metabolism [ 42 ]. Transcription factors such as the basic helix–loop–helix (bHLH), R2R3-MYB, and the WD40 proteins lead to the activation, and differential temporal and spatial expression of the structural genes necessary in the biosynthesis [ 22 , 42 , 43 ]. Furthermore, concomitant increase in the synthesis of quercetin also occurs alongside the synthesis of lignin, mainly due to expression upregulation of the same set of enzymes pertaining to the phenylpropane metabolic pathway, pathway responsible for the synthesis of both molecules [ 44 ].…”
Section: Quercetinmentioning
confidence: 99%
See 1 more Smart Citation
“…Nearly all flavonoids contain the common diphenylpropane (C6-C3-C6) carbon framework with two aromatic rings (A-ring and B-ring) interconnected by a three-carbon heterocyclic pyran ring (C-ring chain) [ 2 , 3 ]. Based on the degree of heterocyclic C-ring oxidation, the position of hydroxyl and methyl groups on the A- and B-rings and the degree of modifications (including glycosylation, acylation and polymerization ), flavonoids can be chiefly categorized into six classes: flavones, flavanones, flavonols, flavanols, anthocyanins and isoflavones [ 3 , 4 ]. An enormous amount of research during the last few decades has revealed that flavonoids, as the most bioactive plant secondary metabolites, might exhibit a wide range of physiological functions in plant growth, development, reproduction and stress defense [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, over 9000 flavonoid molecules have been identified from various plant species [ 4 ], and the molecular mechanisms of enzymes catalyzing flavonoid biosynthesis have also been well established, such as in Arabidopsis thaliana , Solanum lycopersicum (tomato), Glycine max , Phaseolus vulgaris and Vitis vinifera [ 2 , 38 , 39 ]. O. sativa (rice), as an experimental system for monocots, is the most economically important food staple crop for human nutrition [ 35 ].…”
Section: Introductionmentioning
confidence: 99%